Michael Longley’s Father: Memory, Mourning and History - Barry Sloan (Estudios Irlandeses, 2012)
Michael Longley’s father has been a recurring presence in the poet’s work from his earliest to his most recent collection. This paper examines the exceptional strength of that bond reflected in the varied and changing ways in which the poet has responded to it – memorizing and mourning his loss; discovering through his father’s First World War stories a means of memorialising loss of life in contemporary conflicts and a way of facing the history of the twentieth century; confronting his own ageing and sense of mortality; and marking the specific, but also representative, generational history of his family. Close readings of key poems are offered to highlight Longley’s skills in meeting his own exacting standards of aesthetic propriety and moral and social responsibility for writers of elegy in order to avoid either exploitation of tragedy and loss, or facile gestures of consolation.